"We shall remove the Sun": Henry More's Neoplatonic adaptation of Jacob Böhme's philosophy. - Muratori, Cecilia (British Journal for the History of Philosophy, 2024)
This article presents a detailed analysis of how the Cambridge Platonist Henry More (1614–1687) adapted the philosophy of the German mystic Jacob Böhme (1575–1624). For More, Böhme's errors can be amended only by intervening radically in his philosophical system, discussing not what Böhme said, but what he should have said. In particular, the essay studies how and why More, in Censura, altered a scheme used by Böhme in his Clavis to explain visually the core of his philosophical insight. It claims that this intervention, which consists mainly in moving the position of the Sun in the scheme, turns Böhme's circular metaphysical system, in which the Sun, or fire, was the fulcrum of a perpetual movement, into a Neoplatonic system of emanation. In so doing, More fashions himself as a "Böhme redivivus", showing to his readers that the only way of making sense of Böhme is to read him in Neoplatonic terms. The removal of the Sun from its original place in the scheme thus exemplifies More's unease with Böhme's conception of the Sun as fully embedded in the dynamic interplay of light and darkness, and shows that More's interpretation of Böhme involves a full operation of rewriting.